Ultraviolet light affects the color vocabulary: evidence from 834 languages - Dediu, Dan (Frontiers in Psychology, 2023)
It has been suggested that people living in regions with a high incidence of ultraviolet light, particularly in the B band (UV-B), suffer a phototoxic effect during their lifetime. This effect, known as lens brunescence, impacts negatively the perception of visible light in the “blue” part of the spectrum, which, in turn, reduces the probability that the lexicon of languages spoken in such regions contains a word specifically denoting ‘blue’. This hypothesis has been recently tested using a database of 142 unique populations/languages using advanced statistical methods, finding strong support. Here, this database is extended to 834 unique populations/languages in many more language families (155 versus 32) and with a much better geographical spread, ensuring a much better representativity of present-day linguistic diversity. Applying similar statistical methods, supplemented with novel piecewise and latent variable Structural Equation Models and phylogenetic methods made possible by the much denser sampling of large language families, found strong support for the original hypothesis, namely that there is a negative linear effect of UV-B incidence on the probability that a language has a specific word for ‘blue’. Such extensions are essential steps in the scientific process and, in this particular case, help increase our confidence in the proposal that the environment (here, UV-B incidence) affect language (here, the color lexicon) through its individual-level physiologic effects (lifetime exposure and lens brunescence) amplified by the repeated use and transmission of language across generations.